Alloying and modification of stainless steels by powerful plasma streams - Makhlaj, V. A.; Aksenov, N. N.; Byrka, O. V.; Chunadra, A. G.; Herashchenko, S. S.; Malykhin, S. V.; Mikhailov, I. F.; Sereda, K. N.; Surovitskiy, S. V. (My University, 2016)
The stainless steel surfaces coated of tungsten have been alloyed and modified with powerful QSPA Kh-50 plasma streams. The plasma streams exposures result in modification of steel-based materials and formation of re-solidified layers. The changes of substrate texture were also registered. Phase characterized by body-centered cubic lattice appeared due to recrystallization of affected material. Thus, the favorable conditions were created for penetration of tungsten into the stainless steel bulk. Growth of lattice parameter was observed as result of plasma irradiation of coated samples. It's indication of tungsten penetration into the depth of substrates.

Поверхні з нержавіючої сталі з покриттям з вольфраму були леговані і модифіковані потужними плазмовими потоками в КСПП Х-50. Опромінення потоком плазми призводить до модифікації матеріалів на основі сталей і формування повторно затверділого шару. Зміни текстури підкладки були також зареєстровані. Фаза, яка характеризується об'ємно центрованою кубічною решіткою, з'явилася внаслідок рекристалізації опроміненого матеріалу. Таким чином, були створені необхідні умови для проникнення вольфраму в нержавіючу сталь. Зростання параметра решітки спостерігався в результаті плазмового опромінення зразків з покриттям. Це вказує на проникнення вольфраму в глибину субстратів.
Легування і модифікація нержавіючої сталі потужними потоками плазми
Keywords: alloying; plasma streams; stainless steels; tungsten; recrystallization; хімічні речовини; рекристалізація; субстрати; плазмове опромінення; вольфрам